A Cascaded MEMS Amplitude Demodulator for Large Dynamic Range Application in RF Receiver - Hao Yan; Xiaoping Liao; Chenglin Li; Chen Chen (Micromachines, 2021)
An amplitude demodulator with a large dynamic range, based on microelectromechanical systems (MEMS), is proposed in this paper. It is implemented as a cascade of a capacitive and a thermoelectric sensor. Two types of the transducer can improve the measurement range and enhance the overload capacity. This MEMS-based demodulation is realized by utilizing the square law relationship and the low-pass characteristic during the electromechanical and thermoelectric conversion. The fabrication of this device is compatible with the GaAs monolithic microwave integrated circuit (MMIC) process. Experiments show that this MEMS demodulator can realize the direct demodulation of an amplitude modulation (AM) signal with a carrier frequency of 0.35–10 GHz, and cover the power range from 0 to 23 dBm. This MEMS demodulator has the advantages of high power handling capability and zero DC power consumption.